Pengaruh Penerapan Media Pembelajaran Digital Marketing Terhadap Minat Berwirausaha Siswa Kelas XI PPLG - Ekarini, Fitria; Indah Idamawarti, Itamara; Kuswanto, Heri (Universitas Hamzanwadi, 2024)
This study aims to analyze the impact of digital marketing educational media on students' entrepreneurial interest. It uses a quantitative approach with an experimental research type and a Quasi Experiment design with a Pretest-Posttest Control Group Design format. The sample consists of 36 students from class XI PPLG 1 as the control group and 36 students from class XI PPLG 2 as the experimental group. The results from the simple linear regression test show a significance value of 0.063 for the control group and 0.005 for the experimental group, with 0.063 > 0.05 and 0.005 < 0.05. Therefore, in the control group, H0 is accepted and H1 is rejected, indicating no effect of digital marketing implementation on students' entrepreneurial interest. In contrast, in the experimental group, H0 is rejected and H1 is accepted, demonstrating an effect of digital marketing implementation on students entrepreneurial interest